Interjections and emojis in Nigerian online communication. Issue 4 (15th March 2021) - Honkanen, Mirka; Müller, Julia
Abstract: This study investigates Nigerian and English interjections and emojis used for expressing surprise in Nigerian online communication. Interested in the factors influencing the choice between a shocked emoji and an English or Nigerian interjection, we apply automated emotion analysis and a language detection measurement we developed for an 840‐million‐word web forum corpus to test the influence of these and further variables on the choice of a surprise item. Our multinomial regression model suggests that the probability of Nigerian interjections is higher in messages containing Nigerian Pidgin, informal orthographically lengthened words, and positive emotions, while the shocked emoji occurs in negative contexts, in messages by established forum members, and alongside other emojis. The sad emoji, however, favors English‐language interjections, as do high arousal and emotionally laden words. Moreover, we argue that interjections are not only a spoken phenomenon but occur in any type of communication characterized by interactivity and emotional involvement.